Great Books of the Western World (Book 13) : Plutarch : The Lives of the Noble Grecians and Romans - Editor in Chief Adler, Mortimer J. (Chicago Encyclopaedia Britannica, 1993)
Plutarch's Parallel Lives, written at the beginning of the second century A.D., form a brilliant social history of the ancient world. They were originally presented in a series of books that gave an account of one Greek and one Roman life, followed by a comparison of the two: Theseus and Romulus, Alcibiades and Coriolanus, Demosthenes and Cicero, Demetrius and Antony. Plutarch was interested in the personalities of his subjects and on the way their characters molded their actions, leading them to tragedy or victory. He was a moralist of the highest order. 'It was for the sake of others that I first commenced writing biographies' he says, 'but I find myself proceeding and attaching myself to it for my own; the virtues of these great men serving me as a sort of looking-glass, in which I may see how to adjust and adorn my own life' Plutarch was a man of immense erudition who had traveled widely throughout the Roman Empire, and the Lives are richly anecdotal and full of detail. They were the principal source of Shakespeare's Roman plays.
Include Index
Keywords: Rome (Empire) -- Greece